Exercise dosages for the management of generalized anxiety disorder: A scoping review - Leander, Natalie (University of the Witwatersrand, Johannesburg, 2024)
Objective: This review was conducted to map the extent of evidence relating to the dosage of exercise for anxiolytic effect, in youth and adolescents with Generalized Anxiety Disorder (GAD). Introduction: Exercise is known for its benefit to people living with depression and anxiety in adult populations. Less is known about the differences in exercise prescriptions used for the management of anxiety subtypes in younger populations. The rationale for this topic in adolescents and youths, living with GAD was to ascertain the extent to which this cohort has been studied regarding the use of exercise in the treatment of anxiety and which dosages were used. Inclusion criteria: All studies with participants aged 10-24 years of age with a GAD diagnosis, were considered, where exercise was used as part of the management of their anxiety. No restrictions were placed on study types. A scoping review was performed using the JBI methodology. Databases searched included Pubmed, PEDro, Cochrane database of systematic reviews and Cinahl Ultimate along with grey literature databases. No time restrictions were applied, and all types of research articles were considered. The charted data was tabulated using a modified JBI data extraction instrument. The initial result of 728 results was reduced to four studies that met with inclusion criteria. The final four studies had populations in the upper range of between 18 to 24 only. No applicable data was found in the 10 to 17-year age range. The exercise types used in these four studies were treadmill running, Pilates, lower limb strengthening and dynamic cycling. Two studies incorporated a single bout of vigorous treadmill running for 30 minutes. One study did a single bout of beginner Pilates for 30 minutes and the last study used lower limb strengthening and dynamic cycling biweekly for six weeks. The literature on exercise dosage for the management of GAD in adolescents and youth is severely limited. Data on exercise for specific subtypes of anxiety in adolescents and youth seems to be limited in general as well. This is an important area for research as anxiety starts in early childhood and GAD in particular has a peak age of onset of 15 years. It seems feasible to try and approach anxiety in youth and adolescents with non-invasive therapies such as exercise but there is a definite gap in the literature regarding its use in managing GAD
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Physiotherapy Johannesburg, 2024
Keywords: Anxiety; Exercise; Anxiolytic; UCTD; SDG-3: Good health and well-being